Implementasi Pendidikan Prenatal dalam Upaya Menumbuhkan Kecintaan pada Al-Qur’an - Firgina Amelia Nurhusni; Dadan Nugraha (AL-KAINAH: Journal of Islamic Studies, 2023)
Prenatal education is education given to children before birth or from the time they are in the womb until the child is born. The research method uses literature review, technical in the literature review method includes systematic identification, analysis of documents containing information related to the study problem through some of the available literature. Prenatal education is important because it stimulates the brain so that it is able to store memories and respond to stimuli from outside so that the benefits of children having intelligence are also a child who will be easily directed to good things, easy to memorize lessons, easy to be advised if they make mistakes, easier to interact also have confidence. In the implementation of prenatal education, careful preparation is needed so that parents must develop a curriculum in the form of determining teaching materials usually related to Islamic religious teachings, for example: hijaiyah letters, memorizing short letters and selected letters, stories of the Prophet. The techniques used in prenatal education are audio and tactile techniques. Also other methods used can be in the form of dialogue, story telling, prayer, worship and so forth.